Unsaturated polyester‐toughened epoxy composites: Effect of sisal fiber on thermal and dynamic mechanical properties. Issue 3 (23rd June 2015) - Paluvai, Nagarjuna Reddy; Mohanty, Smita; Nayak, S.K.
Abstract : In the present study, the mechanical and thermal properties of sisal fiber‐reinforced unsaturated polyester (UP)‐toughened epoxy composites were investigated. The sisal fibers were chemically treated with alkali (NaOH) and silane solutions in order to improve the interfacial interaction between fibers and matrix. The chemical composition of resins and fibers was identified by using Fourier‐transform infrared spectroscopy. The UP‐toughened epoxy blends were obtained by mixing UP (5, 10, and 15 wt%) into the epoxy resin. The fiber‐reinforced composites were prepared by incorporating sisal fibers (10, 20, and 30 wt%) within the optimized UP‐toughened epoxy blend. Scanning electron microscopy was used to analyze the morphological changes of the fibers and the adhesion between the fibers and the UP‐toughened epoxy system. The results showed that the tensile and flexural strength of (alkali‐silane)‐treated fiber (30 wt%) ‐reinforced composites increased by 83% and 55%, respectively, as compared with that of UP‐toughened epoxy blend. Moreover, thermogravimetric analysis revealed that the (alkali‐silane)‐treated fiber and its composite exhibited higher thermal stability than the untreated and alkali‐treated fiber systems. An increase in storage modulus and glass transition temperature was observed for the UP‐toughened epoxy matrix on reinforcement with treated fibers. The water uptake behavior of both alkali and alkali‐silane‐treated fiber‐reinforced composites is found to be less as compared with the untreated fiber‐reinforced composite. J. VINYL ADDIT. TECHNOL., 23:188–199, 2017. © 2015 Society of Plastics Engineers